Fuel cell double catalytic layer cathode, preparation method and fuel cell

By adopting a dual-catalytic layer structure in fuel cells, combining a catalytic layer with a high specific surface area and a low specific surface area, the problem of difficult to take into account both the mass transfer capacity and the water retention capacity of the cathode catalytic layer are solved, and optimized water management under high current density and The mass transfer capability improves the performance of fuel cells.

CN118800919BActive Publication Date: 2025-02-11CATARC AUTOMOTIVE TEST CENT TIANJIN CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411281684.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2025-02-11
Estimated Expiration
2044-09-13

AI Technical Summary

Technical Problem

The prior art is difficult to take into account the mass transfer capability and water retention capability of the cathode layer of the fuel cell, especially under low humidity or non-humidification operating conditions, resulting in performance loss.

Method used

A dual catalytic layer structure is adopted, wherein the first catalytic layer is arranged on the side of the proton exchange membrane, has a high specific surface area and a small secondary pore size, and the second catalytic layer is arranged on the side of the gas diffusion layer, has a lower specific surface area. and larger secondary pore sizes. This structure is prepared by spraying to ensure close contact between the catalytic layer and the proton exchange membrane and effective water management.

Benefits of technology

It realizes optimized water management and mass transfer capabilities under high current density, reduces the attenuation of fuel cell performance under extreme operating conditions, and improves the power density and energy conversion efficiency of fuel cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118800919B_ABST
    Figure CN118800919B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of fuel cells, and in particular, provides a fuel cell double-catalyst layer cathode, a preparation method and a fuel cell. The fuel cell double-catalyst layer cathode comprises a first catalytic layer for being arranged on one side of a proton exchange membrane and a second catalytic layer for being arranged on one side of a gas diffusion layer; the first catalytic layer and the second catalytic layer are each independently a platinum-cobalt alloy catalytic layer based on a carbon carrier; the specific surface area of ​​the first catalytic layer is 500-900 m 2 / g, the secondary pore size is 20~50nm; the specific surface area of ​​the second catalytic layer is 50~150 m 2 / g, and the secondary pore size is 70-100nm. The present invention can take into account both the mass transfer capacity and the water retention capacity of the cathode catalyst layer of the fuel cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of fuel cells, and in particular to a fuel cell double-catalyst layer cathode, a preparation method and a fuel cell. Background Art

[0002] Due to the synergistic effect of platinum and cobalt, platinum-cobalt alloy catalysts have excellent catalytic activity and can accelerate the key reactions in fuel cells, thereby effectively improving the power density and energy conversion efficiency of fuel cells. In addition, platinum-cobalt catalysts can also help reduce the use of precious metal platinum, thereby reducing the cost of fuel cells and providing strong support for the commercial application of fuel cells. However, low humidity or non-humidified operating conditions will lead to a decrease in the ionic conductivity of the catalyst layer and the proton exchange membrane and an increase in ohmic losses, further exacerbating performance losses. In general, fuel cells need to be humidified, but this will increase the cost of the fuel cell system. In addition, water management inside the fuel cell is particularly important at high current density. Excessive water content will cause liquid water to block the pore structure of the catalyst layer, resulting in a significant decrease in mass transfer capacity, which restricts the improvement of fuel cell performance. Therefore, it is of great significance to take into account both the mass transfer capacity and water retention capacity of the cathode catalyst layer of the fuel cell.

[0003] In view of this, the present invention is proposed. Summary of the invention

[0004] The purpose of the present invention is to provide a fuel cell double catalytic layer cathode, a preparation method and a fuel cell to solve the problem that the prior art cannot take into account both the mass transfer capacity and the water retention capacity of the fuel cell cathode catalytic layer.

[0005] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0006] In a first aspect, the present invention provides a fuel cell double catalyst layer cathode, comprising a first catalyst layer for being arranged on one side of a proton exchange membrane and a second catalyst layer for being arranged on one side of a gas diffusion layer;

[0007] The first catalytic layer and the second catalytic layer are each independently a platinum-cobalt alloy catalytic layer based on a carbon carrier; the specific surface area of ​​the first catalytic layer is 500-900 m 2 / g, the secondary pore size is 20~50nm; the specific surface area of ​​the second catalytic layer is 50~150 m 2 / g, and the secondary pore size is 70~100nm.

[0008] As a further preferred technical solution, the carbon carrier includes acetylene black, Ketjen black or conductive carbon black.

[0009] As a further preferred technical solution, the Pt loading in the cathode is 0.1-0.3 mg / cm2 .

[0010] In a second aspect, the present invention provides a method for preparing the above-mentioned fuel cell double-catalyst layer cathode, comprising the following steps:

[0011] The carbon support, water, platinum source and cobalt source are uniformly mixed to obtain a platinum-cobalt precursor aqueous solution;

[0012] Transferring the platinum-cobalt precursor aqueous solution to a rotary evaporator for evaporation to dryness;

[0013] The powder obtained by evaporation is calcined in an inert atmosphere, and then acid-washed and dried to obtain a platinum-cobalt alloy catalyst based on a carbon support;

[0014] The carbon-supported platinum-cobalt alloy catalyst, water, an organic solvent, and an ionomer solution are uniformly mixed to obtain a first catalytic layer ink and a second catalytic layer ink, respectively;

[0015] The first catalyst layer ink and the second catalyst layer ink are sprayed on the proton exchange membrane in sequence to obtain a fuel cell double catalyst layer cathode.

[0016] As a further preferred technical solution, the carbon carrier, water, platinum source and cobalt source are mixed under sealed conditions, with a stirring speed of 300-500 rpm, a stirring temperature of 25-35°C and a stirring time of 12-36 h; the concentration of the platinum-cobalt precursor aqueous solution is 3-3.5 g / L.

[0017] As a further preferred technical solution, the rotation speed of the rotary evaporation equipment is 100-150 rpm, the evaporation temperature is 50-60° C., and the vacuum condition is one atmosphere.

[0018] As a further preferred technical solution, the calcination temperature is 500-800°C, the calcination time is 2-6 hours, and the acid washing is carried out using 0.5-1 M acid solution and water in sequence.

[0019] As a further preferred technical solution, when the carbon-based platinum-cobalt alloy catalyst, water, organic solvent, and ionomer solution are mixed, the concentration of the mixed solution is 4-8 mg / mL, the mixing method is ultrasonic dispersion, and the ionomer content accounts for 10-30 wt% of the total mass of the solid material.

[0020] As a further preferred technical solution, the spraying temperature is 70-90°C.

[0021] In a third aspect, the present invention provides a fuel cell, comprising the above-mentioned fuel cell dual-catalytic layer cathode, or a fuel cell dual-catalytic layer cathode prepared by the above-mentioned fuel cell dual-catalytic layer cathode preparation method.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The fuel cell double-catalyst layer cathode provided by the present invention has a secondary pore gradient from the proton exchange membrane to the gas diffusion layer, which facilitates gas-liquid two-phase flow at high current density and optimizes water management and mass transfer capacity under high load. Among them, the first catalyst layer close to the proton exchange membrane side has a higher specific surface area, which can store part of the water generated by the reaction during the operation of the fuel cell. In the case of no humidification of the cathode, it is beneficial to maintain the hydration of the proton exchange membrane and the ion conductivity of the catalyst layer, and weaken the attenuation of the fuel cell performance under extreme operating conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The pore size distribution of the catalyst is measured and fitted by the fully automatic specific surface area analyzer in Example 1.

[0025] Figure 2 The pore size distribution of the catalyst layer is measured by mercury intrusion porosimetry and obtained by fitting in Example 1.

[0026] FIG3 (a) shows the polarization curves and power density curves of the cathode double catalytic layer and the traditional single-layer cathode catalytic layer measured under the cathode full humidification condition in Example 1.

[0027] FIG3( b ) shows the polarization curves and power density curves of the double cathode catalyst layer and the conventional single cathode catalyst layer in Example 1 measured under non-humidified cathode conditions.

[0028] Figure 4 The cathode double catalytic layer in Example 1 is 2 A / cm 2 Electrochemical impedance spectroscopy test results at different relative humidity under different current densities.

[0029] FIG5( a ) shows the pore size distribution of the catalyst in Example 2, measured using a fully automatic specific surface area analyzer and obtained through fitting.

[0030] FIG5( b ) is the pore size distribution of the catalyst layer measured by mercury intrusion porosimetry and obtained by fitting in Example 2.

[0031] FIG6 (a) shows the pore size distribution of the catalyst measured by a fully automatic specific surface area analyzer and obtained by fitting in Example 3.

[0032] FIG6( b ) is the pore size distribution of the catalyst layer measured by mercury intrusion porosimetry and obtained by fitting in Example 3.

[0033] FIG7( a ) is a polarization curve and a power density curve measured under full humidification conditions after adjusting the order of the catalyst layers in Example 1 in Comparative Example 2. FIG.

[0034] FIG7( b ) is a polarization curve and a power density curve measured under non-humidification conditions after adjusting the order of the catalyst layers in Example 1 in Comparative Example 2.

[0035] Figure 7 (c) shows the 2 A / cm2 measured under full humidification conditions between Example 1 and after adjusting the order of the catalytic layers in Comparative Example 2. 2 Electrochemical impedance spectroscopy test results at different current densities.

[0036] Figure 7 (d) shows the 2 A / cm2 measured under non-humidification conditions after adjusting the order of the catalyst layers in Example 1 in Comparative Example 2. 2 Electrochemical impedance spectroscopy test results at different current densities.

[0037] FIG8( a ) is a polarization curve and a power density curve measured under full humidification conditions for Example 1 and the mixed catalytic layer in Comparative Example 3.

[0038] FIG8( b ) is the polarization curve and power density curve measured under full humidification conditions for Example 1 and the mixed catalytic layer in Comparative Example 3. DETAILED DESCRIPTION

[0039] The embodiments of the present invention will be described in detail below in conjunction with examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer.

[0040] As one aspect of the present invention, the present invention provides a fuel cell double catalyst layer cathode, comprising a first catalyst layer for being arranged on one side of a proton exchange membrane and a second catalyst layer for being arranged on one side of a gas diffusion layer;

[0041] The first catalytic layer and the second catalytic layer are each independently a platinum-cobalt alloy catalytic layer based on a carbon carrier; the specific surface area of ​​the first catalytic layer is 500-900 m 2 / g, the secondary pore size is 20~50nm; the specific surface area of ​​the second catalytic layer is 50~150 m 2 / g, and the secondary pore size is 70~100nm.

[0042] The specific surface area of ​​the first catalytic layer is typically but not limited to 500, 550, 600, 650, 700, 750, 800, 850 or 900 m 2 / g, preferably 700~900 m 2 The secondary pore size of the first catalytic layer is typically, but not limited to, 20, 30, 40 or 50 nm. The specific surface area of ​​the second catalytic layer is typically, but not limited to, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140 or 150 m2 / g, preferably 50~120 m 2 The secondary pore size of the first catalytic layer is typically, but not limited to, 70, 80, 90 or 100 nm.

[0043] The above-mentioned fuel cell double-catalyst layer cathode has a secondary pore gradient from the proton exchange membrane to the gas diffusion layer, which facilitates gas-liquid two-phase flow at high current density and optimizes water management and mass transfer capacity under high load. Among them, the first catalyst layer close to the proton exchange membrane side has a higher specific surface area, which can store part of the water generated by the reaction during the operation of the fuel cell. In the case of no humidification of the cathode, it is beneficial to maintain the hydration of the proton exchange membrane and the ion conductivity of the catalyst layer, and weaken the attenuation of fuel cell performance under extreme operating conditions.

[0044] In an optional embodiment, the carbon support includes acetylene black, Ketjen black or conductive carbon black.

[0045] In an optional embodiment, the Pt loading in the cathode is 0.1-0.3 mg / cm 2 Typical but non-limiting Pt loadings in the cathode are 0.1, 0.15, 0.2, 0.25 or 0.3 mg / cm 2 .

[0046] As another aspect of the present invention, the present invention provides a method for preparing a double-catalyst layer cathode of a fuel cell, comprising the following steps:

[0047] The carbon support, water, platinum source and cobalt source are uniformly mixed to obtain a platinum-cobalt precursor aqueous solution;

[0048] Transferring the platinum-cobalt precursor aqueous solution to a rotary evaporator for evaporation to dryness;

[0049] The powder obtained by evaporation is calcined in an inert atmosphere, and then acid-washed and dried to obtain a platinum-cobalt alloy catalyst based on a carbon support;

[0050] The carbon-supported platinum-cobalt alloy catalyst, water, an organic solvent, and an ionomer solution are uniformly mixed to obtain a first catalytic layer ink and a second catalytic layer ink, respectively;

[0051] The first catalyst layer ink and the second catalyst layer ink are sprayed on the proton exchange membrane in sequence to obtain a fuel cell double catalyst layer cathode.

[0052] The above “respectively obtaining a first catalytic layer ink and a second catalytic layer ink” means that the carbon-supported platinum-cobalt alloy catalysts in the first catalytic layer ink and the second catalytic layer ink are different, and thus the obtained inks are also different.

[0053] The preparation method is simple and easy, with low cost. The carbon carrier, water, chloroplatinic acid aqueous solution and cobalt nitrate hexahydrate are uniformly mixed in sequence, and then evaporated and reduced at high temperature to obtain the desired catalytic material. The material has the desired structure, good electrical conductivity and excellent oxygen reduction performance. The cathode catalytic layer prepared by spraying the catalytic layer ink can be firmly bonded to the proton exchange membrane, which is conducive to the effective proton conduction between the catalytic layer and the proton exchange membrane.

[0054] Optionally, the platinum source includes one of chloroplatinic acid, platinum nitrate, and potassium chloroplatinate, and the cobalt source includes one of cobalt nitrate, cobalt chloride, and cobalt carbonate.

[0055] In an optional embodiment, the carbon carrier, water, platinum source and cobalt source are mixed under sealed conditions, with a stirring speed of 300-500 rpm, a stirring temperature of 25-35°C, and a stirring time of 12-36 hours; the concentration of the platinum-cobalt precursor aqueous solution is 3-3.5 g / L. The above stirring speed is typically but not limited to 300, 350, 400, 450 or 500 rpm, the stirring temperature is typically but not limited to 25, 26, 27, 28, 29, 30, 31, 32, 33, 34 or 35°C, the stirring time is typically but not limited to 12, 14, 16, 18, 20, 22, 24, 26, 28, 30, 32, 34 or 36 hours, preferably 18-24 hours, and the concentration of the platinum-cobalt precursor aqueous solution is typically but not limited to 3, 3.1, 3.2, 3.3, 3.4 or 3.5 g / L.

[0056] In an optional embodiment, the rotation speed of the rotary evaporator is 100-150 rpm, the evaporation temperature is 50-60°C, and the vacuum condition is one atmosphere. The above rotation speed is typically but not limited to 100, 110, 120, 130, 140 or 150 rpm; the evaporation temperature is typically but not limited to 50, 51, 52, 53, 54, 55, 56, 57, 58, 59 or 60°C.

[0057] In an optional embodiment, the calcination temperature is 500-800°C, the calcination time is 2-8 hours, and the acid washing is sequentially carried out with 0.5-1 M acid solution and water. The calcination temperature is typically but not limited to 500, 600, 700 or 800°C, the calcination time is typically but not limited to 2, 3, 4, 5, 6, 7, 8 hours, and the concentration of the acid solution is typically but not limited to 0.5, 0.75 or 1 M. The acid solution can be a sulfuric acid, nitric acid or hydrochloric acid solution.

[0058] Optionally, the drying after pickling can be carried out in a vacuum drying oven, or in a forced air drying oven.

[0059] In an optional embodiment, when the carbon-supported platinum-cobalt alloy catalyst, water, organic solvent, and ionomer solution are mixed, the concentration of the mixed solution is 4-8 mg / mL, the mixing method is ultrasonic dispersion, and the ionomer content accounts for 10-30 wt% of the total mass of the solid material. The concentration of the mixed solution is typically but not limited to 4, 5, 6, 7 or 8 mg / mL; the ionomer content is typically but not limited to 10 wt%, 20 wt% or 30 wt% of the total mass of the solid material.

[0060] In this embodiment, the platinum-cobalt alloy precursor solution is mixed by stirring, and the catalyst layer ink is mixed by ultrasonic dispersion. Stirring is conducive to long-term mixing treatment, and ultrasonic dispersion is efficient and has a good mixing effect in a short time.

[0061] Optionally, the organic solvent is an alcohol, preferably isopropanol. Isopropanol is widely available, miscible with water, and has a suitable dielectric constant.

[0062] In an optional embodiment, the spraying temperature is 70-90° C. The spraying temperature is typically but not limited to 70, 80 or 90° C.

[0063] As another aspect of the present invention, the present invention further provides a fuel cell, comprising the above-mentioned fuel cell double catalytic layer cathode, or a fuel cell double catalytic layer cathode prepared by the above-mentioned fuel cell double catalytic layer cathode preparation method.

[0064] It should be noted that the above fuel cell also includes an anode, which needs to be prepared separately. The preparation method is the same as that of the cathode. The anode catalyst material is replaced with a commercial 20wt% Pt / C catalyst, the ionomer content is 10~30wt%, and the Pt loading is 0.1mgPt / cm 2 about.

[0065] The present invention is further described in detail below with reference to the embodiments and comparative examples.

[0066] Example 1

[0067] A fuel cell is prepared by the following method:

[0068] Weigh 100 mg of acetylene black carbon carrier and immerse it in 30 mL of deionized water and 8.7 mL of chloroplatinic acid solution (19.3 mmol / L), mix and stir for 10 minutes, then add 51.6 mg of cobalt nitrate hexahydrate, stir overnight for 24 hours, and take rotary evaporation after mixing evenly. Select a rotation speed of 150 rpm and an evaporation temperature of 55 ° C. The obtained black powder was transferred to a high-temperature tube furnace, heated to 600 ° C in a mixed gas of 95% vol argon + 5% vol hydrogen, calcined at high temperature for 6 hours, and then naturally cooled to room temperature to obtain a platinum-cobalt alloy catalyst. Finally, the catalyst was acid-washed with 0.5 M sulfuric acid at 80 ° C for 8 hours to remove unstable cobalt species. The catalyst was then washed with deionized water until the filtrate pH = 7. Transfer to a vacuum drying oven and dry overnight at 60 ° C. The obtained catalyst is recorded as PtCo / AB.

[0069] The synthesis method of another catalyst is similar to the above one, except that the carbon support is replaced with Ketjen Black 600JD. The obtained catalyst is recorded as PtCo / KB-600JD.

[0070] The obtained platinum-cobalt alloy catalyst was mixed with Nafion solution (Dupon), deionized water and isopropanol, and ultrasonically prepared into a cathode platinum-cobalt alloy catalyst ink, wherein the concentration of the catalyst ink was 10 mg / mL, Nafion accounted for 20wt% of the total solid mass, and the volume ratio of water to isopropanol was 1:4.

[0071] Pt / C catalyst (40% Pt, Johnson Matthey) was mixed with Nafion solution (Dupon), deionized water and isopropanol, and ultrasonically prepared into anode platinum carbon catalyst ink. The concentration of the catalyst ink was 10 mg / mL, Nafion accounted for 25wt% of the total solid mass, and the volume ratio of water to isopropanol was 1:4.

[0072] On one side of the Gore membrane (12 μm, Gore), Pt / C catalyst ink was sprayed as the anode, and on the other side near the membrane, platinum-cobalt alloy catalyst ink with Ketjen Black 600JD as the carbon carrier was preferentially coated, and then platinum-cobalt alloy catalyst ink with acetylene black as the carbon carrier was sprayed as the cathode. Among them, the Pt loading in the anode catalyst layer was 0.1 mg / cm 2 The Pt loading in the cathode catalyst layer is 0.2 mg / cm 2 The spraying temperature was 80°C (it should be noted that the platinum loading of the two catalysts in the cathode catalyst layer was evenly distributed)

[0073] After the catalytic layer is sprayed, carbon paper is added to the anode and cathode to make a membrane electrode, and then assembled into a fuel cell for testing. The test conditions are: hydrogen flow rate 300 mL / min, air flow rate 1500 mL / min, back pressure 100kPa, test temperature 80℃, anode 100% RH, and two operating conditions for the cathode, 0 and 100% RH respectively.

[0074] All parameters in this embodiment are within the preferred range of the present invention.

[0075] The nitrogen isotherm adsorption curve of the obtained platinum-cobalt alloy catalyst was measured using a fully automatic specific surface area analyzer, and the pore size distribution of the catalyst was obtained by fitting, such as Figure 1 As shown in the figure, it can be seen that the pores inside the catalyst with acetylene black as the carbon carrier are composed of a small part of 1-2nm micropores and 2-3nm mesopores. After calculation, its BET specific surface area is 55.1 m 2 / g. The pores inside the catalyst with Ketjen Black 600JD as the carbon carrier are composed of a large number of 1-2nm micropores and 2-10nm mesopores. After calculation, its BET specific surface area is 820 m 2 / g.

[0076] The pore structures of the two catalyst layers were characterized by mercury intrusion porosimetry. Figure 2 As shown. According to mercury intrusion analysis, the Pt-Co / AB catalyst layer provides a continuous pore size in the range of 40~200nm, with an average pore size of about 95nm, which indicates that the Pt-Co / AB catalyst layer is full of larger secondary pore structures. The Pt-Co / KB-600JD catalyst layer curve has a typical flat profile, indicating that the catalyst with a high specific surface area and porous structure forms a catalyst layer with fewer and smaller secondary pore structures.

[0077] Figure 3 (a) shows the measured polarization curve and power density curve. Compared with the traditional single-layer cathode catalyst layer, under the condition of full humidification of the cathode, the double-catalyst layer cathode in this embodiment increases the maximum power density of the fuel cell by 12.7%. This is due to the optimization of mass transfer capacity caused by the gradient structure of gradually increasing pores from the proton exchange membrane to the gas diffusion layer, which significantly increases the peak power density. Figure 3 (b) shows the measured polarization curve and power density curve. Compared with the traditional single-layer cathode catalyst layer, under the condition of non-humidification of the cathode, the double-catalyst layer cathode in this embodiment increases the maximum power density of the fuel cell by 20.2%. The improvement in peak power density is not only attributed to the pore gradient of the cathode catalyst layer to enhance the mass transfer performance, but also closely related to the "water storage" effect of the high specific surface area catalyst layer close to the proton exchange membrane side. 2 A / cm 2 The test results of electrochemical impedance spectroscopy under current density are as follows: Figure 4As shown in the figure, as the relative humidity decreases from 100% to 0%RH, the high-frequency resistance of the cathode dual catalyst layer does not change significantly. The high specific surface area catalyst layer has the ability to retain water. Under non-humidification conditions, it can store part of the water generated by the reaction, so that the proton conductivity of the proton exchange membrane and the cathode catalyst layer will not be significantly reduced, effectively alleviating the impact of ohmic loss and maintaining the fuel cell performance within a certain range.

[0078] Example 2

[0079] A fuel cell, which is different from Example 1 in that acetylene black is replaced with XC-72 carbon carrier in this example, and the obtained catalyst is recorded as PtCo / XC-72. During spraying, Pt / C catalyst ink is sprayed on one side of a Gore membrane (12 μm, Gore) as an anode, and the other side close to the membrane is preferentially coated with platinum-cobalt alloy catalyst ink with Ketjen Black 600JD as a carbon carrier, and then platinum-cobalt alloy catalyst ink with XC-72 as a carbon carrier is sprayed as a cathode.

[0080] The nitrogen isotherm adsorption curve of the platinum-cobalt alloy catalyst was measured using a fully automatic specific surface analyzer, and the pore size distribution of the catalyst was obtained by fitting. As shown in Figure 5 (a), it can be seen that the pores inside the catalyst with XC-72 as the carbon carrier are composed of micropores of 1-2 nm. After calculation, its BET specific surface area is 140.1 m 2 / g.

[0081] The pore structure of the above catalyst layer was characterized by mercury intrusion, as shown in Figure 5 (b). According to the mercury intrusion analysis, the Pt-Co / XC-72 catalyst layer provides a continuous pore size in the range of 20-200 nm, with an average pore size of about 65 nm, which indicates that the secondary pores of the Pt-Co / XC-72 catalyst layer are smaller than those of the Pt-Co / AB catalyst layer.

[0082] Using the polarization curve and power density measured in this example, compared with the traditional single-layer cathode catalyst layer, under the condition of full cathode humidification, the double-catalyst layer cathode in this example increases the maximum power density of the fuel cell by 5.8%. Under the condition of non-humidified cathode, the double-catalyst layer cathode in this example increases the maximum power density of the fuel cell by 13.7%.

[0083] Example 3

[0084] A fuel cell, different from Example 1, in this example, acetylene black is replaced by Ketjen black 300J carbon carrier, and another catalyst is a platinum-cobalt alloy catalyst with acetylene black as carbon carrier. During spraying, Pt / C catalyst ink is sprayed on one side of a Gore membrane (12 μm, Gore) as an anode, and the other side close to the membrane is preferentially coated with a platinum-cobalt alloy catalyst ink with Ketjen black 300J as a carbon carrier, and then a platinum-cobalt alloy catalyst ink with acetylene black as a carbon carrier is sprayed as a cathode.

[0085] The nitrogen isotherm adsorption curve of the obtained platinum-cobalt alloy catalyst was measured using a fully automatic specific surface analyzer, and the pore size distribution of the catalyst was obtained by fitting, as shown in Figure 6 (a). It can be seen that the pores inside the catalyst with Ketjen Black 300J as the carbon carrier are composed of micropores of 1-2nm and mesopores of 2-3nm. After calculation, its BET specific surface area is 750 m 2 / g.

[0086] The pore structure of the above catalyst layer was characterized by mercury intrusion, as shown in Figure 6(b). According to mercury intrusion analysis, the Pt-Co / XC-72 catalyst layer provides a continuous pore size range of 10-200 nm, with an average pore size of about 30 nm, which again indicates that catalysts with high specific surface area and porous structure tend to form a catalyst layer with fewer and smaller secondary pore structures.

[0087] Using the polarization curve and power density measured in this example, compared with the traditional single-layer cathode catalyst layer, under the condition of full cathode humidification, the double-catalyst layer cathode in this example increases the maximum power density of the fuel cell by 8.2%. Under the condition of non-humidified cathode, the double-catalyst layer cathode in this example increases the maximum power density of the fuel cell by 9.6%.

[0088] Example 4

[0089] A fuel cell, which is different from Example 1 in that in the catalyst ink of this example, Nafion accounts for 20wt% of the solid mass of the platinum-cobalt alloy catalyst with acetylene black as the carbon carrier, and Nafion accounts for 30wt% of the mass of the platinum-cobalt alloy catalyst with Ketjen Black 600JD as the carbon carrier.

[0090] Using the polarization curves and power densities measured in this embodiment, under the condition of 100% RH of the cathode, the maximum power density of the fuel cell increased by 9.4%. Under the condition of non-humidified cathode, the double catalytic layer cathode in this embodiment increased the maximum power density of the fuel cell by 16.4%, which was attributed to the high ionomer content near the membrane side optimizing the proton conduction of the proton exchange membrane and the hydration capacity of the catalytic layer.

[0091] Example 5

[0092] A fuel cell, which is different from Example 1 in that in the catalyst ink of this example, Nafion accounts for 20wt% of the solid mass of the platinum-cobalt alloy catalyst with acetylene black as the carbon carrier, and Nafion accounts for 10wt% of the mass of the platinum-cobalt alloy catalyst with Ketjen Black 600JD as the carbon carrier.

[0093] Using the polarization curves and power densities measured in this embodiment, under the condition of 100% RH of the cathode, the maximum power density of the fuel cell increased by 7%. Under the condition of non-humidified cathode, the double catalytic layer cathode in this embodiment increased the maximum power density of the fuel cell by 13.7%, which was attributed to the high ionomer content near the membrane side optimizing the proton conduction of the proton exchange membrane and the hydration capacity of the catalytic layer.

[0094] Example 6

[0095] A fuel cell, which is different from Example 1 in that in the catalyst ink of this example, Nafion accounts for 30wt% of the solid mass of the platinum-cobalt alloy catalyst with acetylene black as the carbon carrier, and Nafion accounts for 20wt% of the mass of the platinum-cobalt alloy catalyst with Ketjen Black 600JD as the carbon carrier.

[0096] Using the polarization curve and power density measured in this embodiment, under the condition of full humidification of the cathode, the double catalyst layer cathode in this embodiment increases the maximum power density of the fuel cell by 2.3%, and the increase in the ionomer content makes the secondary pore structure of the catalyst layer close to the gas diffusion layer smaller, and the mass transfer capacity is reduced under high current density conditions. Under the condition of non-humidification of the cathode, the double catalyst layer cathode in this embodiment increases the maximum power density of the fuel cell by 13.7%.

[0097] Example 7

[0098] A fuel cell, which is different from Example 1 in that in the catalyst ink of this example, Nafion accounts for 10wt% of the solid mass of the platinum-cobalt alloy catalyst with acetylene black as the carbon carrier, and Nafion accounts for 20wt% of the mass of the platinum-cobalt alloy catalyst with Ketjen Black 600JD as the carbon carrier.

[0099] Using the polarization curve and power density measured in this embodiment, under the condition of full humidification of the cathode, the double catalyst layer cathode in this embodiment increases the maximum power density of the fuel cell by 10.5%, and the reduction of the ionomer content slightly increases the secondary pore structure of the catalyst layer near the gas diffusion layer compared with the optimal ionomer content, but the reduction of the ionomer content weakens the proton conduction capacity of the catalyst layer, and the performance decreases. Under the condition of non-humidification of the cathode, the double catalyst layer cathode in this embodiment increases the maximum power density of the fuel cell by 15.6%.

[0100] Example 8

[0101] A fuel cell, different from Example 1, in this embodiment, the Pt loading in the anode catalyst layer is 0.1 mg / cm 2 , while the Pt loading in the cathode catalyst layer was reduced to 0.1 mg / cm 2 The spraying temperature was 80°C. (The platinum loading of the two catalysts in the cathode catalyst layer was still evenly distributed)

[0102] Using the polarization curve and power density measured in this embodiment, under the condition of full humidification of the cathode, the double catalytic layer cathode in this embodiment increases the maximum power density of the fuel cell by 5.8%. Thanks to the reduction in the thickness of the catalytic layer caused by the reduction in the platinum loading of the cathode catalytic layer, the water retention effect of the catalytic layer is significantly increased under the condition of non-humidification of the cathode, and the double catalytic layer cathode in this embodiment increases the maximum power density of the fuel cell by 20%.

[0103] Example 9

[0104] A fuel cell, different from Example 1, in this embodiment, the Pt loading in the anode catalyst layer is 0.1 mg / cm 2 , and the Pt loading in the cathode catalyst layer increased to 0.3 mg / cm 2 The spraying temperature was 80°C. (The platinum loading of the two catalysts in the cathode catalyst layer was still evenly distributed)

[0105] Using the polarization curve and power density measured in this embodiment, under the condition of full humidification of the cathode, thanks to the increase in the platinum loading of the catalyst layer, the double catalyst layer cathode in this embodiment increases the maximum power density of the fuel cell by 15.2%. Under the condition of non-humidification of the cathode, the increase in the thickness of the catalyst layer leads to a weakening of the water retention effect, and the double catalyst layer cathode in this embodiment increases the maximum power density of the fuel cell by 13.6%.

[0106] Example 10

[0107] A fuel cell, which is different from Example 1 in that in this example, the spraying temperature is reduced to 70°C.

[0108] Using the polarization curve and power density measured in this embodiment, under the condition of full cathode humidification, the double catalytic layer cathode increases the maximum power density of the fuel cell by 11.1%. Under the condition of non-humidified cathode, the double catalytic layer cathode in this embodiment increases the maximum power density of the fuel cell by 19.8%.

[0109] Embodiment 11

[0110] A fuel cell, which is different from Example 1 in that in this example, the spraying temperature is increased to 90°C.

[0111] Using the polarization curve and power density measured in this embodiment, under the condition of full cathode humidification, the double catalytic layer cathode increases the maximum power density of the fuel cell by 12.5%. Under the condition of non-cathode humidification, the double catalytic layer cathode in this embodiment increases the maximum power density of the fuel cell by 20%.

[0112] Example 12

[0113] A fuel cell, which is different from Example 1, is that in this example, the black powder obtained by rotary evaporation is heated to 500° C. in a mixture of 95% vol argon and 5% vol hydrogen, and is calcined at high temperature for 6 hours.

[0114] Using the polarization curve and power density measured in this embodiment, under the condition of full cathode humidification, the double catalytic layer cathode increases the maximum power density of the fuel cell by 4.7%. Under the condition of non-humidified cathode, the double catalytic layer cathode in this embodiment increases the maximum power density of the fuel cell by 9.6%.

[0115] Embodiment 13

[0116] A fuel cell, which is different from Example 1, is that in this example, the black powder obtained by rotary evaporation is heated to 700° C. in a mixture of 95% vol argon and 5% vol hydrogen, and is calcined at high temperature for 6 hours.

[0117] Using the polarization curve and power density measured in this embodiment, under the condition of full cathode humidification, the double catalytic layer cathode increases the maximum power density of the fuel cell by 7%. Under the condition of non-humidified cathode, the double catalytic layer cathode in this embodiment increases the maximum power density of the fuel cell by 12.3%.

[0118] Comparative Example 1

[0119] A fuel cell is prepared by the following method:

[0120] Pt / C catalyst (40% Pt, Johnson Matthey) was mixed with Nafion solution (Dupon), deionized water and isopropanol, and platinum-carbon catalyst ink was prepared by ultrasound. The concentration of the anode catalyst ink was 10 mg / mL, Nafion accounted for 25wt% of the total solid mass, and the volume ratio of water to isopropanol was 1:4. The concentration of the cathode catalyst ink was 10 mg / mL, Nafion accounted for 20wt% of the total solid mass, and the volume ratio of water to isopropanol was 1:4.

[0121] Pt / C catalyst ink was sprayed on both sides of the Gore membrane (12 μm, Gore) as the anode and cathode respectively. The Pt loading in the anode catalyst layer was 0.1 mg / cm 2The Pt loading in the cathode catalyst layer is 0.2 mg / cm 2 The spraying temperature was 80°C.

[0122] After the catalytic layer is sprayed, carbon paper is added to the anode and cathode to make a membrane electrode, and then assembled into a fuel cell for testing. The test conditions are: hydrogen flow rate 300 mL / min, air flow rate 1500 mL / min, back pressure 100kPa, test temperature 80℃, anode 100%RH, cathode two operating conditions, respectively 0 and 100%RH. The test results are shown in Figure 3.

[0123] Comparative Example 2

[0124] A fuel cell, which is different from Example 1 in that Nafion in this comparative example accounts for 20wt% of the solid mass of the platinum-cobalt alloy catalyst.

[0125] On one side of the Gore membrane (12μm, Gore), Pt / C catalyst ink is sprayed as the anode, and on the other side close to the membrane, platinum-cobalt alloy catalyst ink with acetylene black as the carbon carrier is preferentially coated, and then platinum-cobalt alloy catalyst ink with Ketjen Black 600JD as the carbon carrier is sprayed as the cathode. This catalyst layer is named PtCo / AB-PtCo / KB-600JD.

[0126] FIG7 (a) is the measured polarization curve and power density curve. Compared with the cathode catalyst layer of Example 1, under the condition of full humidification of the cathode, the maximum power density of the dual-catalyst layer cathode in this embodiment is reduced by 11.8%. FIG7 (b) is the polarization curve and power density curve measured under the condition of non-humidification of the cathode. The maximum power density of the dual cathode catalyst in this embodiment is reduced by 22.4%. This embodiment shows that the gradient of the pores of the dual catalyst layer gradually increasing from the proton exchange membrane to the gas diffusion layer is conducive to the improvement of the peak power density. At the same time, the use of a high specific surface area catalyst layer close to the membrane side is conducive to the maintenance of the fuel cell performance under non-humidification conditions.

[0127] Figure 7 (c) shows the condition of 100%RH, 2A / cm 2 From the electrochemical impedance spectrum at the time of , it can be found that when the catalyst layer has a gradient characteristic of gradually increasing pores from the proton exchange membrane to the gas diffusion layer, a smaller mass transfer resistance is obtained. On the contrary, when the pores of the catalyst layer gradually decrease from the proton exchange membrane to the gas diffusion layer, an obvious mass transfer resistance appears. The same phenomenon can also be observed under non-humidified conditions in Figure 7 (d). Under non-humidified conditions, the high-frequency resistance of the PtCo / AB-PtCo / KB-600JD catalyst layer also increases significantly, indicating the "water retention" ability of the high specific surface area catalyst layer close to the proton exchange membrane side.

[0128] Comparative Example 3

[0129] A fuel cell, which is different from Example 1 in that in this comparative example, Nafion accounts for 20wt% of the solid mass of the platinum-cobalt alloy catalyst.

[0130] Pt / C catalyst ink was sprayed on one side of the Gore membrane (12 μm, Gore) as the anode, and a mixed platinum-cobalt alloy catalyst ink with acetylene black and Ketjen Black 600JD as carbon carriers was sprayed on the other side as the cathode.

[0131] Figure 8 (a) is the measured polarization curve and power density curve. Compared with the cathode catalyst layer of Example 1, under the condition of full cathode humidification, the maximum power density of the double-catalyst layer cathode in this embodiment is reduced by 13.2%. Figure 8 (b) is the polarization curve and power density curve measured under the condition of non-humidified cathode. The maximum power density of the double cathode catalysis in this embodiment is reduced by 28.9%. This embodiment shows that the hybrid double-catalyst layer structure has no optimization effect on the improvement of fuel cell performance.

[0132] Table 1

[0133]

[0134] Although the present invention has been illustrated and described with specific embodiments, it will be appreciated that many other changes and modifications may be made without departing from the spirit and scope of the present invention. Therefore, it is intended to include all such changes and modifications within the scope of the present invention in the appended claims.

Claims

1. A fuel cell double catalytic layer cathode, characterized in that: It includes a first catalyst layer for being arranged on one side of a proton exchange membrane and a second catalyst layer for being arranged on one side of a gas diffusion layer; The first catalytic layer and the second catalytic layer are each independently a platinum-cobalt alloy catalytic layer based on a carbon carrier; the specific surface area of ​​the first catalytic layer is 500-900 m 2 / g, the secondary pore size is 20~50nm; the specific surface area of ​​the second catalytic layer is 50~150 m 2 / g, the secondary pore size is 70~100nm; The carbon carrier includes acetylene black, Ketjen black or conductive carbon black; The Pt loading in the cathode is 0.1-0.3 mg / cm 2 .

2. The method for preparing a fuel cell double-catalyst layer cathode according to claim 1, characterized in that: The following steps are involved: The carbon support, water, platinum source and cobalt source are uniformly mixed to obtain a platinum-cobalt precursor aqueous solution; Transferring the platinum-cobalt precursor aqueous solution to a rotary evaporator for evaporation to dryness; The powder obtained by evaporation is calcined in an inert atmosphere, and then acid-washed and dried to obtain a platinum-cobalt alloy catalyst based on a carbon support; The carbon-supported platinum-cobalt alloy catalyst, water, an organic solvent, and an ionomer solution are uniformly mixed to obtain a first catalytic layer ink and a second catalytic layer ink, respectively; The first catalyst layer ink and the second catalyst layer ink are sprayed on the proton exchange membrane in sequence to obtain a fuel cell double catalyst layer cathode.

3. The method for preparing a fuel cell double-catalyst layer cathode according to claim 2, characterized in that: The carbon carrier, water, platinum source and cobalt source are mixed under sealed conditions, with a stirring speed of 300-500 rpm, a stirring temperature of 25-35° C. and a stirring time of 12-36 h; the concentration of the platinum-cobalt precursor aqueous solution is 3-3.5 g / L.

4. The method for preparing a fuel cell double-catalyst layer cathode according to claim 2, characterized in that: The rotation speed of the rotary evaporation equipment is 100-150 rpm, the evaporation temperature is 50-60° C., and the vacuum condition is one atmosphere.

5. The method for preparing a fuel cell double-catalyst layer cathode according to claim 2, characterized in that: The calcination temperature is 500-800°C, the calcination time is 2-6 hours, and the acid washing is carried out by sequentially using 0.5-1 M acid solution and water.

6. The method for preparing a fuel cell double-catalyst layer cathode according to claim 2, characterized in that: When the carbon-supported platinum-cobalt alloy catalyst, water, an organic solvent, and an ionomer solution are mixed, the concentration of the mixed solution is 4-8 mg / mL, the mixing method is ultrasonic dispersion, and the ionomer content accounts for 10-30 wt% of the total mass of the solid material.

7. The method for preparing a fuel cell double-catalyst layer cathode according to any one of claims 2 to 6, characterized in that: The spraying temperature is 70-90°C.

8. A fuel cell, characterized in that: The invention comprises the fuel cell double catalyst layer cathode as claimed in claim 1, or a fuel cell double catalyst layer cathode prepared by the preparation method of the fuel cell double catalyst layer cathode as claimed in any one of claims 2 to 7.

Citation Information

Patent Citations

  • Low-platinum cathode catalyst layer used for fuel cell and application thereof

    CN102104155A

  • Synthesis method and electro-catalysis application of carbon-loaded platinum-based intermetallic compound nano material

    CN113113623A

  • High-temperature proton exchange membrane fuel cell cathode, preparation method and membrane electrode

    CN116722156A

  • Composite catalyst layer, catalytic membrane electrode, fuel cell and application

    CN116799233A